(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Zygomatic bone is closely associated with the maxilla, frontal, temporal bones which are usually involved when a zygomatic bone fracture occurs. The most common causes of these fractures are from the assaults, road traffic accidents and falls. Aesthetic beauties and functions are greatly hampered with the displacement of the fractured fragments. Objective: To analyze the aetiology, clinical presentations, surgical intervention and complications associated with zygomatic complex (ZC) fractures in a tertiary level healthcare facility. Materials and Methods: This descriptive observational study was carried out in the Oral and Maxillofacial Department, Military Dental Centre, Dhaka during the period of January 2016 to December 2016. Data were obtained from clinical notes and surgical records of the patients using standardized data collection form specifically designed to examine the variables and features of zygomatic complex fractures. Results: Road traffic accidents were the leading cause (75%) of zygomatic fractures. The mean operation time was found 99.5±31.2 minutes with a range from 60 to 125 minutes. Open reduction and two-point internal fixation were employed in more than two-third (67.5%) of the cases. Four (10.0%) patients developed postoperative complications; among them 2(5.0%) cases suffered paresis of temporal branch of facial nerve and trismus. Other complications included paraesthesia, ectropion, scar and palpability of plate. Twenty-five (62.5%) patients were found having limited mouth opening preoperatively and postoperative improvement occurred in 21(52.5%). Thirty three (82.5%) patients had facial asymmetry preoperatively and postoperative improvement occurred in 29(72.5%). Conclusion: More than two-third of the patients received two point fixations. Only four patients out of forty in this study were found having post operative complications. The functional and Aesthetic outcome was found to be fair in terms of improvement in limitation of mouth opening and correction of facial asymmetry. Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 71-74